Retrospective evaluation of poisoning patients in the emergency department [Aci̇l servi̇se başvuran zehi̇rlenme olgularinin geri̇ye dönük anali̇zi̇] - (:unkn) unknown (My University, 2008)
Objective: The purpose of this study was to determine the clinical properties and demographics of patients admitting to the Emergency Department (ED) with intoxication. Patient and Methods: A retrospective study was conducted with poisoning patients admitted to our ED between 1st of June 2005 and 31st of December 2006. Data regarding the age, sex, reason for the intoxication, and presence of psychiatric evaluation were obtained from the patient files. Results: One hundred and forty-seven intoxication cases were admitted to ED. Mean time spent before admission to ED after exposure was 7,61 hours. 78 cases were in the daytime, 69 cases at night. The agent exposed was drugs in 72 of the cases whereas 63 was food and 12 was alcohol. 102 cases were treated in ED and 45 cases were admitted to hospital. Psychiatric evaluation was performed on 65 patients. Conclusion: Demographics of the patients admitting to our ED were similar to the findings of other studies reported from Turkey. Intoxication seems to be the problem of young women and drugs are the most frequent agents. Drug intoxicated cases are younger, report faster to ED and all of them were intended suicide. All of these suicidal cases were admitted to a hospital and psychiatric evaluation was carried out.
Keywords: Emergency Department; Intoxication; Psychiatric evaluation